2021
DOI: 10.3389/fvets.2021.775114
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting of Milk Production in Northern Thailand Using Seasonal Autoregressive Integrated Moving Average, Error Trend Seasonality, and Hybrid Models

Abstract: Milk production in Thailand has increased rapidly, though excess milk supply is one of the major concerns. Forecasting can reveal the important information that can support authorities and stakeholders to establish a plan to compromise the oversupply of milk. The aim of this study was to forecast milk production in the northern region of Thailand using time-series forecast methods. A single-technique model, including seasonal autoregressive integrated moving average (SARIMA) and error trend seasonality (ETS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Moreover, our results revealed that the prediction abilities of the ARIMA and NNAR were approximately comparable. This could be due to the fact that the data set contains both linear and non-linear patterns, and, therefore, the strengths of one model may not provide an advantage over another [ 37 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our results revealed that the prediction abilities of the ARIMA and NNAR were approximately comparable. This could be due to the fact that the data set contains both linear and non-linear patterns, and, therefore, the strengths of one model may not provide an advantage over another [ 37 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the forecasted values were compared to the actual ones in the validation set. In addition, error metrics, including mean absolute percentage error (MAPE), mean absolute scale error (MASE), and root mean square error (RMSE), were calculated using functions from the “Metrics” package in order to measure the predictive abilities of the ARIMA and NNAR models [ 42 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Forecasts for January 2022 to December 2022 were then generated from the training dataset and compared with the actual values within the same period in the test dataset to assess the forecasting model's performance. Second, in an effort to ensure up-to-date and accurate forecasts, it is suggested that the most current data be used for prediction ( 28 , 34 ).Therefore, all time series models were applied to the full dataset to generate forecasts for the following 3 years (January 2023–2025). A schematic representation of the modeling procedure is provided in Figure 1 for clarity.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure the utilization of the most recent data for forecasting, we applied all the final time series models to the full dataset. This approach facilitated the modeling and forecasting of canine rabies cases for the three subsequent years post the last observation data incorporated in this study, as described in ( 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…Even though a study of the spatio-temporal pattern of the outbreak in beef cattle farms was carried out ( 23 ), studies on the epidemiology of LSD outbreaks in dairy farms remain limited, allowing several knowledge gaps, particularly on how the LSD outbreaks distributed among dairy farms in terms of space and time. The findings of the study in beef farming areas ( 23 ) may not be extrapolated to dairy farming areas because beef and dairy cattle farms in Thailand are managed differently ( 31 , 32 ). Furthermore, the spatial distributions of beef and dairy farms differ, with the majority of dairy farming areas being densely populated with dairy farms and beef farms being sparsely populated.…”
Section: Introductionmentioning
confidence: 99%